Sphenoid sinus pneumatization in a sample of Nepalese population: A multidetector computed tomography study. - Lalchan, Subita; Shrestha, Ashish; Jwarchan, Bishnu (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: The purpose of study was to assess the prevalence of different types of pneumatization of sphenoid sinus in the Nepalese population as detected in CT scan of paranasal sinus. Materials and Methods: This study included patients attending radiology department for CT scan of paranasal sinus. The CT images of paranasal sinus were assessed for the type of pneumatization of the sphenoid sinus and type of clival, lateral recess and lesser wing extensions. Results: Most common type of pneumatization found in our study was complete sellar type (61.7%) and partial sellar type was second common type (27.4%). Pre-sellar type of pneumatization was seen in 10.9%. There were no patients with conchal type of pneumatization in our study. The clival extension of pneumatization was seen in 64%, lateral extension was found in 35.4%. and lesser wing type of pneumatization was found in 9.7%. Conclusion: Pre-surgical assessment of types and extension of sphenoid sinus pneumatization helps surgeons in surgical planning and to reduce complications during surgery. The variation in prevalence of sphenoid sinus pneumatization was found between our study population and other different population. This confirms that ethnicity influences types and extension of sphenoid sinus pneumatization.